2016
DOI: 10.1038/srep33881
|View full text |Cite
|
Sign up to set email alerts
|

Transport Phenomena of Water in Molecular Fluidic Channels

Abstract: In molecular-level fluidic transport, where the discrete characteristics of a molecular system are not negligible (in contrast to a continuum description), the response of the molecular water system might still be similar to the continuum description if the time and ensemble averages satisfy the ergodic hypothesis and the scale of the average is enough to recover the classical thermodynamic properties. However, even in such cases, the continuum description breaks down on the material interfaces. In short, mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 59 publications
5
69
1
1
Order By: Relevance
“…In an attempt to improve upon the quantitative accuracy of the PNP-NS equations for nanopore simulations, we developed an extended version of these equations (ePNP-NS) and implemented it in the commercial finite element solver COMSOL Multiphysics (v5.4, www.comsol.com). Our ePNP-NS equations self-consistently take into account 1) the finite size of the ions, 76,78 2) the reduction of ion and water motility close to the nanopore walls, 54,58,79,80,83 and 3) the concentration dependency of ion diffusion coefficients and electrophoretic mobilities, as well as electrolyte viscosity, density and relative permittivity. 87,92,93 Most of these corrections make use of using empirical functions that were fitted to experimental data (Tabs.…”
Section: Governing Equationsmentioning
confidence: 99%
“…In an attempt to improve upon the quantitative accuracy of the PNP-NS equations for nanopore simulations, we developed an extended version of these equations (ePNP-NS) and implemented it in the commercial finite element solver COMSOL Multiphysics (v5.4, www.comsol.com). Our ePNP-NS equations self-consistently take into account 1) the finite size of the ions, 76,78 2) the reduction of ion and water motility close to the nanopore walls, 54,58,79,80,83 and 3) the concentration dependency of ion diffusion coefficients and electrophoretic mobilities, as well as electrolyte viscosity, density and relative permittivity. 87,92,93 Most of these corrections make use of using empirical functions that were fitted to experimental data (Tabs.…”
Section: Governing Equationsmentioning
confidence: 99%
“…For the velocity at the walls, a no-slip boundary condition is used; for the nanoparticles concentration a no-flux boundary condition ensures that no particle is capable of penetrating the wall. It is worth pointing out that in nanofluidics the hydrodynamic slippage of the fluid is also possible due to the effect of the properties of the interface, such as wettability and roughness [29,35,37,84,85]. Table 1.…”
Section: The Expanded Forms Of the Governing Equations And The Boundamentioning
confidence: 99%
“…Usually the thermal conductivity and viscosity of nanofluids is considered to be a function which may depend on the nanoparticles concentration and the properties of the base fluids [13,14,[28][29][30]. According to the review articles [31,32], the thermal conductivity and viscosity usually increase non-linearly in the function of nanoparticle volume concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies supported the importance of Brownian motion for the enhanced thermal conductivity of nanofluids [35,36], there are other researchers against it [37,38]. As for the liquid layer at the liquid/particle interface, molecular dynamic simulations [39][40][41][42] discovered water density fluctuation near the solid surface representing the liquid layer and could explain the thermal behavior such as temperature jump on the surface, while some studies [43][44][45] indicated that the liquid layer might not influence the thermal behavior of nanofluids. In addition, Keblinski et al [44] found that ballistic heat transport still could not explain the anomalous thermal conductivity enhancements either.…”
Section: Introductionmentioning
confidence: 99%